2019
DOI: 10.1017/ice.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of uncomplicated acute respiratory tract infection management in veterans: A national utilization review

Abstract: Background:Antibiotics are overprescribed for acute respiratory tract infections (ARIs). Guidelines provide criteria to determine which patients should receive antibiotics. We assessed congruence between documentation of ARI diagnostic and treatment practices with guideline recommendations, treatment appropriateness, and outcomes.Methods:A multicenter quality improvement evaluation was conducted in 28 Veterans Affairs facilities. We included visits for pharyngitis, rhinosinusitis, bronchitis, and upper respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…Our study's findings agree with prior reports on EDs and UCCs that have demonstrated substantial clinician-level variation in antibiotic-prescribing and frequent antibiotic use for likely viral ARIs. 5,6,10,11,20,21 In line with prior VHA studies, we detected a high rate of antibiotic use for acute bronchitis and sinusitis. 10,20 In general, making comparisons across studies is difficult because some studies did not stratify antibiotic-prescribing rates by site of care (eg, ED versus primary care).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study's findings agree with prior reports on EDs and UCCs that have demonstrated substantial clinician-level variation in antibiotic-prescribing and frequent antibiotic use for likely viral ARIs. 5,6,10,11,20,21 In line with prior VHA studies, we detected a high rate of antibiotic use for acute bronchitis and sinusitis. 10,20 In general, making comparisons across studies is difficult because some studies did not stratify antibiotic-prescribing rates by site of care (eg, ED versus primary care).…”
Section: Discussionsupporting
confidence: 86%
“…5,6,10,11,20,21 In line with prior VHA studies, we detected a high rate of antibiotic use for acute bronchitis and sinusitis. 10,20 In general, making comparisons across studies is difficult because some studies did not stratify antibiotic-prescribing rates by site of care (eg, ED versus primary care). Other studies included children or The 2017 guidelines from the Global Initiative for COPD recommend 5-7 d of antibiotics for acute exacerbations of COPD that meet specified criteria.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Potential infectious complications (ie, Clostridioides difficile infections, pneumonia, meningitis, mastoiditis, or facial cellulitis) were identified by a new outpatient or inpatient diagnostic code for these conditions within 30 days following the index visit (eTable S7). [9][10][11] Return visits for gastrointestinal-related adverse antibiotic events were identified by outpatient visits or inpatient admissions with diagnostic codes consistent with potential gastrointestinal-related adverse antibiotic events (ie, diarrhea, colitis, hepatitis, nausea) for visits that occurred within 14 days after the index acute sinusitis visit if the patient did not have a similar diagnostic code within 6 months preceding the visit (eTable S7). 10 Hospitalizations were defined by an admission date that occurred between 1 and 30 days following the index visit.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior chart review of 715 cases of acute sinusitis identified using the same administrative codes, 79% of patient visits with a diagnostic code for acute sinusitis had at least 1 sinusitis symptom documented although only 38% had documentation of IDSA criteria for prescribing antibiotics. 9 To account for clinicians preferentially treating select patients with amoxicillin-clavulanate and to increase causal inference of the retrospective design, we propensitymatched treatment groups. Guideline-suggested criterion for preferentially prescribing amoxicillin-clavulanate over amoxicillin (eg, temperature, frontal sinusitis, comorbidity, age) were used to estimate treatment effects; however, it is possible that unmeasured confounding impacted the results such as healthcare practitioner typewhich despite propensity-matching, was independently associated with select outcomes.…”
Section: Limitationsmentioning
confidence: 99%